PILIHAN DIKSI DALAM KONTESTASI PILPRES 2024 DALAM PERSPEKTIF ANALISIS WACANA KRITIS SEBAGAI PENINGKATAN MUTU PENDIDIKAN LITERASI - Ni nyoman ayu suciartini; Payuyasa, I Nyoman (UHN IGB Sugriwa Denpasar, 2024)
The diction or terms used in the 2024 presidential election battle are some deliberately coined, while others emerge inadvertently, which can lead to multiple interpretations and meanings. Candidate pairs and, on the other hand, can also decrease electability in the political atmosphere. This study aims to analyze popular diction in the 2024 presidential election, both from social media and the bustling reality in society. This research employs a qualitative descriptive research design with the assistance of data collection methods such as observation, documentation, and literature review. The analytical tool used is Discourse Analysis. The results of this study indicate that the most popular diction often contains meanings that, when dissected using critical discourse analysis, reveal several perspectives related to the significance of the diction. Terms such as